New Zealand and Australian species of the genus Leptochiton (Mollusca: Polyplacophora) - Sirenko, Boris (Zootaxa, 2020)
Eighteen species of the chiton genus Leptochiton are present in Australian and New Zealand waters. Leptochiton beui n. sp. and L. marshalli n. sp. are introduced as new to science. Leptochiton laurae and L. cf. opiparus are here recorded for the first time from New Zealand waters. The present material allowed to obtain new information about the number of aesthetes, the girdle armature as well as about the radula morphology in several species. A considerable variability in the valve shape of Leptochiton subantarcticus was observed leading to the consideration of L. deecresswellae being a junior synonym of this species. Nine of the eighteen Leptochiton species are found around New Zealand and nine belong to the Australian region. With the possible exception of L. opiparus, both regions do not share any species.